The Entry Selection System in Indonesia’s Public High Schools: Quo vadis - Taqwa, Muhamad Dzadit; Putra, M. Irfan Dwi; Putra, Edmond Wangtri (LAW REFORM, 2023)
The selection mechanism for students seeking admission into public high schools still leaves the question: is it going to solve problems or even worsen them? The zoning, age, and affirmation bases were initially oriented to be an inclusive selection system based on the concept of equity. Conversely, these bases lead to new problems, such as (1) the disappearance of a fair selection mechanism based on merit, (2) the inability of students from low-quality educational backgrounds to compete with students from high-quality educational backgrounds, (3) the challenges experienced by teachers in adjusting the quality gap between the students selected by the merit-based system and those selected by the current system, (4) the damaged school culture, and (5) the occurrence of legal manipulation. Using the legal normative approach, the aim of the study analyzed this issue through the right and freedom of education. The result that the status quo system is not in line with the freedom of education, and even creates new problems. The government should have improved the quality of the education infrastructures such as teachers, curriculum, and school facilities, before focusing on the access to education. This mechanism becomes an unfair hurdle on their right to and freedom of education. The government to carefully review and re-examine the status quo system; the end might be a significant revision on the existing regulations.